Color Doppler ultrasound-guided PTBD with and without metal stent implantation by endoscopic control: prospective success and early adverse event rates - Schmitz, D.; Grosse, A.; Hallscheidt, P.; Roseneck, A.; Niemeyer, J.; Rudi, J. (Zeitschrift für Gastroenterologie, 2015)
Objective: There are just a few reports on Color Doppler Ultrasound-guided PTBD with and without metal stent implantation by endoscopic control. Ultrasound guidance facilitates percutaneous bile duct access and avoids severe adverse events. Internal biliary drainage rate in PTBD should be as high as possible as endoscopic ultrasound-guided cholangiodrainage (EUCD) offers internal drainage regularly. We report our prospective study analyzing success, internal drainage and adverse event rates.Materials and methods: Between June 2009 and November 2014 overall 63 PTBDs were performed prospectively in 37 patients (18 m, 19f; age on average: 72 years) with benign (9 %) and malignant (91 %) bile duct obstruction. Ultrasound was used in combination with fluoroscopic guidance. Whenever possible, primary or early secondary metal stent implantation via PTBD by endoscopic control was performed as a one step-procedure.Results: 38 of 41 (93 %) initial PTBDs (in four patients PTBD was performed twice) were successful. 22 of 63 PTBDs were follow-up examinations with different interventions. In 34 of 38 successful (89 %) PTBDs, an internal drainage (or metal stent) was implanted. 12 metal stent implantations via PTBD were performed under endoscopic control. Just 2 (5 %) permanent external drainages were inserted. In 63 performed PTBDs 5 (7.9 %) early major adverse events (no severe intrahepatic bleeding) were documented and treated without any procedure related death. When metal stent implantation was performed via PTBD no adverse event was documented.Conclusion: Color Doppler guided PTBD is an effective and safe method for biliary drainage avoiding severe adverse events. Primary or early secondary metal stent implantation via PTBD reduces complication risks additionally. Endoscopic control of stent implantation via PTBD is helpful for optimal stent placement.
Keywords: perkutane transhepatische Cholangiodrainage (PTCD); Gallenwegsobstruktion; Ultraschall